Is there a link between climate change scepticism and populism? An analysis of web tracking and survey data from Europe and the US. Issue 10 (27th July 2022) - Yan, Pu; Schroeder, Ralph; Stier, Sebastian
ABSTRACT: Climate change and populism are two major phenomena in contemporary politics. Recent successes of populist parties and politicians, especially in Europe and in the US, have given rise to extensive debates in the academic literature and beyond. Yet the link between populism and climate change scepticism (henceforth 'scepticism'), has so far received little attention. This paper examines the link between scepticism and populism by means of a unique dataset: a survey and detailed web browsing histories of participants from France, Germany, Italy, Spain, the US, and the UK. The web tracking data includes more than 150 million website visits over a period of three months and the survey contains questions about political attitudes and attitudes towards climate change. We analyse the 8893 websites which contained 'climate change' and its cognates in the URLs and link these website visits and the content of these websites to the political attitudes and climate change orientation of those who visited them. The contribution is both methodological (linking surveys and web tracking data, including cross-country comparison) and substantive (uncovering links between populists, their climate change orientations, and the content of related websites they visited). Our analysis demonstrates the value of computational methods in political communication research and provides insights into the link between populists and climate change scepticism.